HUBUNGAN AGRESSIVE DRIVING BEHAVIOR PENGEMUDI SEPEDA MOTOR DENGAN KECELAKAAN LALU LINTAS (STUDI PADA SISWA SMA DI KABUPATEN SIDOARJO) - Mazroh Ilma Soffania (Universitas Airlangga, 2018)
Road traffic accident was the public health problem that can decrease public health status. Most of the road traffic acccident involving motorcyclist and mostly among people around 15-19 years old. Agressive driving behavior was one of the factors causing road traffic accidents. The aim of this study to analize the relationship between motorcyclist’s agressive driving behavior with road traffic accidents. This research was analytic observational research with case-control design. The population was senior high school student who riding motorcycle aged ≥ 17 years old in Kabupaten Sidoarjo. Population were divided into two groups, namely case group and control group. Case group were respondents who had road traffic accidents while control group were respondents who never had a road traffic accidents in the last year. The number of respondens were involved 24 respondents in case group and 48 respondents in control group. Sampling were purposive sample in case group and matching sampling in control group by age and sex. The result of analysis using chi-square test (α = 5 %) showed that agressive driving behavior in motorcyclist has significant relationship of road traffic accidents (p= 0,0006; OR= 5,320). Senior high school students were encouraged to managed time and more prioritised safety while driving to avoid traffic accidents.